Metrological references for person ability in memory tests. (December 2021) - Melin, J.; Cano, S.J.; Göschel, L.; Fillmer, A.; Lehmann, S.; Hirtz, C.; Flöel, A.; Pendrill, L.R.
Abstract: To ensure reliable diagnosis and treatment consistently throughout healthcare, metrological quality assurance is essential. There are, however, many observations in the social sciences and healthcare, such as the memory tests studied here, which have been 'claimed' to be measurements but in fact have not been fully metrologically legitimated. We have already argued in favour of extending traditional metrological underlying principles to cover social measurements, including the development of construct specification equations (CSE) considered as 'recipes for certified reference materials (CRM)' for traceability, analogous to CRMs in metrology in chemistry. Although the CSE approach has to date been used mostly to explain and validate test item attributes, this paper turns to focus on causal explanations of person characteristics. We describe methods and preliminary results developed in the European EMPIR NeuroMET projects, which may be used for providing quality assured measurement of disease progression and treatment benefits for patients with neurodegenerative conditions.